New Genus and Species of Empheriidae (Insecta: Psocodea: Trogiomorpha) and Their Implication for the Phylogeny of Infraorder Atropetae - Li, Sheng; Yoshizawa, Kazunori; Wang, Qiuzhu; Ren, Dong; Bai, Ming; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Two species of psocids discovered from the Mid-Cretaceous Burmese amber, Latempheria kachinensis Li, Yoshizawa, and Yao, gen. et sp. nov. and Burmempheria curvatavena Li, Yoshizawa, and Yao, sp. nov., are described and assigned to the Empheriidae (Trogiomorpha: Atropetae) family. A phylogenetic analysis of the infraorder Atropetae is conducted based on 38 morphological characters of three outgroups and fifteen ingroups, which supported the monophyly of Atropetae including fossil and extant taxa. In the phylogenetic result, all the genera of fossil families Empheriidae and Archaeatropidae form a monophyletic group, sister to the extant members of Atropetae. The two fossil families also share a lot of similarities in morphology, locality, and geological period. Recently discovered fossil species exhibited combined morphological characters of both families. Based on these observations and the results of the phylogenetic analysis, Archaeatropidae is treated here as a new junior synonym of Empheriidae.